THE PSYCHOLOGY OF FEEDBACK AND ITS IMPACT ON THE EFFECTIVENESS OF MEDICAL EDUCATION - Mirzaeva Sh.R. (Web of Journals Publishing, 2025)
In the context of the rapid development of medical education, the study of feedback psychology becomes particularly relevant as one of the key factors influencing the effectiveness of the educational process. This article aims to analyze the psychological features of perception, interpretation, and use of feedback by medical students, as well as identify its impact on their educational motivation, professional development, and the formation of clinical thinking. It examines the types of feedback, its role in pedagogical interaction, emotional reactions of students to it, its influence on self-esteem levels and stress tolerance, and psychological and pedagogical conditions conducive to improving feedback effectiveness.
Keywords: Feedback, medical education, learning effectiveness, teacher–student interaction, educational motivation, professional reflection, development of clinical thinking.